Activation of telomerase activity and telomere elongation of host cells by Theileria annulata infection - Liu, Junlong; Zhao, Shuaiyang; Li, Zhi; Zhang, Zhigang; Zhao, Baocai; Guan, Guiquan; Yin, Hong; Luo, Jianxun (Frontiers in Microbiology, 2023)
Theileria annulata-transformed cells share many phenotypes with cancer cells, including uncontrolled proliferation, immortalization, and dissemination. Telomeres are DNA-protein complex at the end of eukaryotic chromosomes that function to maintain genome stability and cell replicative capacity. Telomere length maintenance is primarily dependent on telomerase activity. In up to 90% of human cancer cells, telomerase is reactivated through expression of its catalytic subunit TERT. However, the effect of T. annulata infection on telomere and telomerase activity in bovine cells has not yet been described. In the present study, we confirmed that telomere length and telomerase activity are upregulated after T. annulata infection in three types of cell lines. This change depends on the presence of parasites. After eliminating Theileria from cells with antitheilerial drug buparvaquone, telomerase activity and the expression level of bTERT were decreased. In addition, inhibition of bHSP90 by novobiocin led to decreased AKT phosphorylation levels and telomerase activity, indicating that the bHSP90-AKT complex is a potent factor modulates telomerase activity in T. annulata-infected cells.